TEACHERS’ PERCEPTION IN IMPLEMENTING CURRICULUM REVISION CHALLENGE ON PRIMARY AND SECONDARY LEVELS KTSP VS K13 - Sohibun; Eripuddin (JEE (Journal of English Education), 2017)
This article is intended to provide a foundation, reference and overview of the state of readiness of teachers in considering the application of the new curriculum (Revison of curricullum: KTSP become K-13), as well as provide information on teachers' perceptions of the curriculum. This article is useful for teachers in portrait as well as provides information on the implementation of the curriculum (K-13 and KTSP). The method used in writing this article is to use qualitative and descriptive study of literature. Data obtained through the study of literature and observation using a structured interview to sample some of the teachers at the elementary school level, junior and senior high schools in Rokan Hulu used randomize sampling. After re-analyzed, the use of curriculum in Rokan Hulu found that more teachers agree with the new curriculum (K13) based on the existing system in K-13, but they were found to in RokanHulu itself is more efficient when using the last curricullum (KTSP) because the school facilities and good infrastructure does not support the implementation of the K-13 runs perfectly. Starting from the statement "if you want to K13, must complete infrastructure and support; develop what is there not to upset or partial". Of this paper is known that the curriculum in 2013 demand for teachers at all levels of schools in the district RokanHulu, but in practice advice and inadequate infrastructure that does not yet support the implementation of K13. Thus the authors recommend to education observers to gradually complete infrastructure for the implementation of K13 running properly.